2006
DOI: 10.2106/jbjs.e.00173
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Analgesia Protocol for Total Knee Arthroplasty

Abstract: This multimodal perioperative analgesia protocol that included infiltration of a local anesthetic offered improved pain control and minimal side effects to patients undergoing total knee arthroplasty. Our study also confirmed the safety of the protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
281
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 333 publications
(310 citation statements)
references
References 29 publications
19
281
0
8
Order By: Relevance
“…There are some limitations to our study. First, we used the same protocol of multimodal analgesia for pain control in all patients [16,29]. However, we did not record morphine consumption or consider that in assessing pain.…”
Section: Discussionmentioning
confidence: 99%
“…There are some limitations to our study. First, we used the same protocol of multimodal analgesia for pain control in all patients [16,29]. However, we did not record morphine consumption or consider that in assessing pain.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the study by Badner et al [3], studies using intraarticular injections alone failed to show a reduction of narcotic consumption after surgery [5,16,19,22]. Comparing PAI with narcotics alone, two studies [17,27] found decreased early postoperative pain and morphine consumption (Table 4). Comparing PAI with continuous femoral nerve block, Toftdahl et al [26] reported lower pain and morphine consumption in the PAI group on the first day postsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated sample size of 27 in each group was needed to provide 80% power to detect a clinically meaningful difference of 15 mg morphine consumption from PCA during the first 48 hours [27] between the two groups with a SD of 19.4 mg and alpha error of 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations